Evaluation Program of Inclusive Education In College (Study at Brawijaya University Malang and State Islamic University of Sunan Kalijaga Yogyakarta) - Huda, Alimul; Masrukan, Masrukan; Sulhadi, Sulhadi (Journal of Research and Educational Research Evaluation, 2018)
People with disabilities still have not moved from marginal status and discriminatory treatment, especially to access higher education. In fact, the number of their population continues to increase, along with the many natural disasters, accidents, drug abuse and the consequences of horizontal conflict. Therefore, colleges need to transform themselves into inclusive disability friendly campuses. This study aims to see how far the implementation of inclusive education program in UIN Sunan Kalijaga Yogyakarta and Universitas Brawijaya Malang. This research is a program evaluation with mixed method approach. The results showed that inclusive education programs in universities are running well. Inclusive colleges are universal educational representations intended for everyone regardless of their condition of disability. The realization of inclusive university commitment is realized by preparing qualified human resources, fulfilling accessible facilities, financial support, and making standard operational services for disabled students. Universities have made an accesible learning model for students with disabilities. Inclusive higher education program can increase the potential of students with disabilities both academically, socially and independently. The results of this study can be a reference for universities to change into inclusive. So that students with disabilities can really access higher education without having to fear rejected.